An in-vivo treatment monitoring system for ion-beam radiotherapy based on 28 Timepix3 detectors - Kelleter, Laurent; Marek, Lukas; Echner, Gernot; Ochoa-Parra, Pamela; Winter, Marcus; Harrabi, Semi; Jakubek, Jan; Jäkel, Oliver; Debus, Jürgen; Martisikova, Maria (Scientific reports, 2024)
Ion-beam radiotherapy is an advanced cancer treatment modality offering steep dose gradients and a high biological effectiveness. These gradients make the therapy vulnerable to patient-setup and anatomical changes between treatment fractions, which may go unnoticed. Charged fragments from nuclear interactions of the ion beam with the patient tissue may carry information about the treatment quality. Currently, the fragments escape the patient undetected. Inter-fractional in-vivo treatment monitoring based on these charged nuclear fragments could make ion-beam therapy safer and more efficient. We developed an ion-beam monitoring system based on 28 hybrid silicon pixel detectors (Timepix3) to measure the distribution of fragment origins in three dimensions. The system design choices as well as the ion-beam monitoring performance measurements are presented in this manuscript. A spatial resolution of 4 mm along the beam axis was achieved for the measurement of individual fragment origins. Beam-range shifts of 1.5 mm were identified in a clinically realistic treatment scenario with an anthropomorphic head phantom. The monitoring system is currently being used in a prospective clinical trial at the Heidelberg Ion Beam Therapy Centre for head-and-neck as well as central nervous system cancer patients.
Keywords: Heavy Ion Radiotherapy; celková dávka radioterapie; Charged nuclear fragments; Radiotherapy Dosage; Ion-beam therapy; Phantoms, Imaging; radioterapie těžkými ionty; lidé; In-vivo monitoring; Timepix3; Humans; fantomy radiodiagnostické